Electronic Funds Transfer and Service Delivery in SACCOs: A Case Study of Ng’arisha SACCO, Bungoma, Kenya - Nalyanya, Jacinta; Abuya, Joshua Olang’o; Makokha, Arnety Nangila (Journal of Accounting, Business and Finance Research, 2021)
Electronic funds transfer is generally expected to improve efficiency in funds transfers, payments, reporting, receipting and service delivery in any organization. However, the SACCO Societies Regulatory Authority (SASRA) reports of 2018 show that despite Savings and Credit Cooperatives (SACCOs) having institutionalized electronic operations in their accounting process, efficiency and effectiveness in service delivery remains elusive. The main objective is to determine the effect of electronic funds transfer on service delivery in Ng’arisha SACCO, Bungoma, Kenya. The research was guided by Schumpeter’s theory of innovation and technology acceptance and used descriptive survey research design. The total target population used in the study comprises 121 respondents. Census sampling was used where the entire targeted population was sampled. Data was gathered using questionnaires with closed-ended structured questions that were prepared on a five-point Likert scale. Statistical Package for Social Sciences (SPSS) version 26 software was utilized for data analysis. Data was analyzed in the form of descriptive and inferential statistics. The research hypothesis H01 posits that the transfer of e-funds has no significant effect on service delivery in SACCOs. The model was significant and so the null hypothesis was rejected on the grounds that the transfer of e-funds had a significant and moderately strong positive linear correlation with service delivery in SACCOs. Based on the discoveries, service delivery is crucial in the SACCO industry. As a result, there is a strong link between e-funds transfer practices and Ng’arisha SACCO’s service delivery. The study recommends that SACCOs should employ electronic means of transferring funds for their operations to enhance service delivery.